PENGARUH INFLASI, CADANGAN DEVISA, DAN PENGELUARAN PEMERINTAH TERHADAP JUMLAH UANG BEREDAR M2 DALAM JANGKA PENDEK DAN JANGKA PANJANG PERIODE 1999.Q1-2019.Q4 DI INDONESIA - Lisbetty Lisbetty; Rosyetti Rosyetti; Aulia Fahda Ando (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of inflation, foreign exchange reserves and government expenditure on the money supply M2 in Indonesia in the short and long term period 1999.Q1-2019.Q4. This research was conducted in Indonesia with the aim of using data for the period 1999.Q1-2019.Q4 is to produce accurate estimates and conclusions about the variables studied and to find out the interpretation of the research object using quarterly data for 21 years. The method used in this research is descriptive and quantitative methods. The analysis model used is multiple linear regression analysis (the help of software EViews 10). The data analysis technique used is the error correction model. As for seeing the effect of the independent variable on the dependent variable in the short and long term, the final result will measure the effect of inflation, foreign exchange reserves and government spending on the money supply M2 in Indonesia in the short and long term. The results of this study indicate that in the long run, inflation has a negative and significant effect on the money supply of M2, foreign exchange reserves have a positive but insignificant effect on the money supply of M2 and government expenditure has a positive and significant effect on the money supply of M2 in Indonesia. In the short term, inflation has a negative and significant effect on the money supply of M2, while foreign exchange reserves and government expenditure have a positive and significant effect on the money supply of M2 in Indonesia.Keywords: money supply M2, inflation, foreign exchange reserves, government expenditure, error correction model (ECM).